The rate of dasotraline brain entry is slow following intravenous administration - Lew, Robert; Constantinescu, Cristian C.; Holden, Daniel; Carson, Richard E.; Carroll, Vincent; Galluppi, Gerald; Koblan, Kenneth S.; Hopkins, Seth C. (Psychopharmacology, 2020)
Rationale Drugs that rapidly increase dopamine levels have an increased risk of abuse. Dasotraline (DAS) is a dopamine and norepinephrine reuptake inhibitor characterized by slow oral absorption with low potential for abuse. However, it remains unclear whether intravenous (i.v.) administration would facilitate the rapid elevation of dopamine levels associated with stimulant drugs. Objective To assess the kinetics of DAS across the blood-brain barrier and time to onset of dopamine transporters (DAT) inhibition. Methods We compared the onset of DAT occupancy and the associated elevation of synaptic dopamine levels in rhesus monkey following i.v. administration of DAS or methylphenidate (MPH) using positron emission tomography (PET). Brain entry times were estimated by reductions in [ 18 F]-FE-PE2I binding to DAT in rhesus monkeys. Elevations of synaptic dopamine were estimated by reductions in [ 11 C]-Raclopride binding to D 2 receptors. Results Intravenous administration of DAS (0.1 and 0.2 mg/kg) resulted in striatal DAT occupancies of 54% and 68%, respectively; i.v. administered MPH (0.1 and 0.5 mg/kg) achieved occupancies of 69% and 88% respectively. Brain entry times of DAS (22 and 15 min, respectively) were longer than for MPH (3 and 2 min). Elevations in synaptic dopamine were similar for both DAS and MPH however the time for half-maximal displacement by MPH ( t = 23 min) was 4-fold more rapid than for DAS ( t = 88 min). Conclusions These results demonstrate that the pharmacodynamics effects of DAS on DAT occupancy and synaptic dopamine levels are more gradual in onset than those of MPH even with i.v. administration that is favored by recreational drug abusers.